Factors Influencing Outreach Performance of Microfinance Sector in India. (December 2019) - Singh, Vijeta; Padhi, Puja
In recent years microfinance institutions (MFIs) have been duly recognised as an important component of financial system as MFIs can facilitate the agenda of financial inclusion. MFIs provide unbanked and poor appropriately designed financial products and services. MFIs have addressed the issues concerning supply-side barriers 1 to financial inclusion by enhancing its outreach across the countries/regions. However, outreach performance of MFIs is affected by factors concerning MFIs such as age, size, profitability, efficiency, productivity and portfolio quality, which affect outreach (breadth/depth) of MFIs. The present study has attempted to study the factors affecting outreach performance of MFIs in India. The study using unbalanced panel data for 39 Indian MFIs concludes that age, assets and productivity indicators have affirmative association with outreach performance of MFIs in India.